11C‐Carbonylation through in Situ Generated 11C‐Benzoyl Chlorides with Tetrabutylammonium Chloride as Chloride Source. Issue 18 (12th May 2017) - Dahl, Kenneth; Nordeman, Patrik
Abstract : Aromatic 11 C‐containing acids, amides, esters, and aldehydes were obtained through a novel 11 C‐carbonylative reaction. In the two‐step process, aryl iodides are first reacted with 11 CO and tetrabutylammonium chloride in a palladium‐mediated reaction to yield 11 C‐benzoyl chlorides in situ. The crude mixture is then further treated with either a hydroxide, amine, alcohol, or a hydride in a second vial to furnish the final 11 C‐carbonyl product. The monodentate ligand tri‐ tert ‐butylphosphonium tetrafluoroborate was proven to be crucial for obtaining high radiochemical yields (RCY). A wide range of 11 C‐containing carbonyl compounds were successfully radiolabeled in moderate to excellent RCYs, ranging from 41–93 %. The synthetic retinoic acid tamibarotene was obtained in a RCY of 89 %, whereas the Boc‐protected procainamide was labelled in 68 % RCY, which is a significantly increase (2–3 fold) in RCY compared to other published methods. Abstract : A novel radiochemical method for 11 C‐carbonylation is presented. The two‐step protocol relies on an intermediary 11 C‐benzoyl chloride, which is further reacted with a nucleophile to produce desired amides, benzoic acids, esters, and aldehydes. An increased radiochemical yield (RCY) of [ 11 C]tamibarotene and Boc‐protected [ 11 C]procainamide is obtained by using the developed method.